2022
DOI: 10.54957/jurnalku.v2i1.143
|View full text |Cite
|
Sign up to set email alerts
|

Dewan Direksi, Cash Holding, Nilai Perusahaan: Peran Moderasi Dari Leverage

Abstract: Penelitian ini bertujuan untuk menemukan bukti empiris pengaruh cash holding dan ukuran dewan direksi terhadap nilai perusahaan. Selain itu, penelitian ini juga memasukkan leverage dalam hubungan tersebut.  Penelitian ini menggunakan data perusahaan sektor industri barang konsumsi yang terdaftar di Bursa Efek Indonesia tahun 2015 sampai dengan 2020. Data penelitian diperoleh dari www.idx.co.id, www.financial.yahoo.com, dan website resmi perusahaan. Berdasarkan purposive sampling, sampel yang digunakan dalam pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…In addition, the greater the debt owned will motivate management in saving the cash flow, one of the actions is the value of the company. From the description above, it can be concluded that capital structure positive effect on firm value and does not support research conducted by (Emanuel et al, 2022), (Dharma & Ardiana, 2016) and Dewi & Noviasari, (2017) showing that capital structure negative effect on firm value.…”
Section: Coefficient Of Determination Testmentioning
confidence: 62%
“…In addition, the greater the debt owned will motivate management in saving the cash flow, one of the actions is the value of the company. From the description above, it can be concluded that capital structure positive effect on firm value and does not support research conducted by (Emanuel et al, 2022), (Dharma & Ardiana, 2016) and Dewi & Noviasari, (2017) showing that capital structure negative effect on firm value.…”
Section: Coefficient Of Determination Testmentioning
confidence: 62%
“…The company's substantial reserves of cash, which reassure creditors and investors that the business can meet its commitments, are in an optimal state, demonstrating that the company has enough cash on hand to cover operating expenditures, make new investments, and pay debts. The results of earlier studies done by Chandra & Feliana (2020), Emanuel et al (2022) dan Kerryanto (2015) indicates that having cash on hand increases companies worth. Unlike the research conducted by Nisasmara & Musdholifah (2016) and Rahayu & Asandimitra (2014) shown that a company's worth is unaffected by retaining cash.…”
Section: Figure 1 Average Company Value As Measured By Tobin's Q In T...mentioning
confidence: 88%
“…Therefore, it is crucial for the business to decide on the right quantity of cash (Nofiyanti & Subardjo, 2020). The value of a firm is positively influenced by cash holding, according to prior study by Chandra & Feliana (2020), Emanuel et al (2022) and Kerryanto (2015). H1: Cash holding has a positive effect on firm value Organisations can employ intellectual capital, a broad category of all available resources, to create additional value (Nasution & Ovarni,2021).…”
Section: Hypotesis Developmentsmentioning
confidence: 90%
“…Penelitian ini berbeda dengan penelitian sebelumnya yaitu dengan menguji item khusus di laporan posisi keuangan ketika PSAK 73 diterapkan di Indonesia dikaitkan dengan respon pasar di Indonesia yang masih jarang dilakukan di Indonesia. Penelitian pengujian terhadap nilai perusahaan sebelumnya pada umumnya tidak menguji secara khusus atas dampak penerapan atas standar baru (Emanuel et al, 2022;Geno & Firmansyah, 2022;Haryanto et al, 2018;Nasution, 2020;Salman et al, 2020;Zurriah, 2021).…”
Section: Pendahuluanunclassified